Mode acceleration approach to seismic response of multiply-supported secondary systems. - Rao, V. Surya Chandra (Earthquake engineering & structural dynamics.)
A mode acceleration approach has been proposed for estimating the seismic response of a linear, classically damped, multiply supported secondary system within the framework of a power spectral density function (PSDF)-based stochastic approach, while the primary system is linear and classically damped. Response transfer functions have been formulated in terms of chosen numbers of fixed base modes of the primary and secondary systems. The proposed approach does not involve the determination of combined system properties, and is applicable to the secondary systems with high mass ratios also. Through a few example primary secondary systems and an example band limited white noise excitation, it has been shown that this approach leads to reasonably accurate results when only a few primary and secondary modes are to be considered. The proposed formulation has been used to obtain input data for a decoupled response spectrum analysis of secondary systems. This data accurately accounts for the effects of interaction between the primary and secondary systems. It is shown to lead to substantial reductions in the errors associated with the envelope spectrum method in the case of moderately heavy to heavy secondary systems and when the spatial coupling does not play a major role.